DESENVOLVIMENTO DE MÉTODO ELETROANALÍTICO PARA DETERMINAÇÃO DE GLICEROL EM AMOSTRAS DE BIODIESEL - Silva, Verônica Diniz da (2013)
The presence of glycerol in biodiesel can cause serious problems, such as clogged injectors, emissions of aldehydes and environmental problems in the storage of biodiesel. This work intends to evaluate the electrochemical behavior of glycerol in the aqueous and organic electrochemical impedance technique in order to develop an analytical methodology for the determination of glycerol in biodiesel. Thus the analyzes were performed in an electrochemical system containing two platinum electrodes with geometric areas of 1 cm². Using this system analyzes were made by electrochemical impedance spectrometry for the aqueous and organic. The data obtained for the analyzes conducted in aqueous medium were not satisfactory for the study. However, with respect to the results obtained for the organic medium, they showed a great performance, showing obvious processes diffusional mass transport and a steady increase in the conductivity of the medium acetonitrile / glycerol. Having this increased conductivity also confirmed by measurements of electrical conductivity. From these data, we developed an analytical method for the quantification of glycerol in biodiesel using the technique of electrochemical impedance spectroscopy and electrical conductivity measurements. So the optimized operating parameters for the quantification of glycerol by electrochemical impedance were: 106 Hz a 0,1 Hz frequency range, amplitude of 15 mV and time of Eoc of 20 s. Using those parameters obtained an average concentration of glycerol in the biodiesel samples of 5.55 x 10ˉ³ mol Lˉ¹ , a correlation coefficient of 0.997 and a variation coefficient of 22,4 %. To analyze the electrical conductivity of the samples was used soy biodiesel, which through a simple methodology also quantified the glycerol. Thus the average concentration of glycerol in the samples of soybean biodiesel was 3.5 x 10ˉ4 mol Lˉ¹, for a coefficient of 0.998 and coefficient of variation (CV) of 9.8 %. Throughout this procedure was performed for n equal to 3 replicates, considering a confidence level of 95 %.